2011
DOI: 10.1016/j.bbamcr.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar localization/retention signal is responsible for transient accumulation of histone H2B in the nucleolus through electrostatic interactions

Abstract: The majority of known nuclear proteins are highly mobile. The molecular mechanisms by which they accumulate inside stable compartments that are not separated from the nucleoplasm by membranes are obscure. The compartmental retention of some proteins is associated with their biological function; however, some protein interactions within distinct nuclear structures may be non-specific. The non-specific retention may lead to the accumulation of proteins in distinct structural domains, even if the protein does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 49 publications
4
56
0
Order By: Relevance
“…The antibodies to several proteins (including anti-GFP and anti-FLAG antibodies) properly label their antigens inside the nucleoli, but when the antigen is overexpressed (such as EGFP-FLAG-B23 in the present work), the same antigens cannot be labeled by the same antibodies inside the nucleoli. Similar difficulties have been found with such abundant proteins as B23 (Zatsepina et al 1997;Misteli 2008;Musinova et al 2011; this study). One can speculate that the antibodies that were bound to abundant antigens at the nucleolar periphery created a mechanical barrier against the further penetration into the inner region of the nucleoli.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…The antibodies to several proteins (including anti-GFP and anti-FLAG antibodies) properly label their antigens inside the nucleoli, but when the antigen is overexpressed (such as EGFP-FLAG-B23 in the present work), the same antigens cannot be labeled by the same antibodies inside the nucleoli. Similar difficulties have been found with such abundant proteins as B23 (Zatsepina et al 1997;Misteli 2008;Musinova et al 2011; this study). One can speculate that the antibodies that were bound to abundant antigens at the nucleolar periphery created a mechanical barrier against the further penetration into the inner region of the nucleoli.…”
Section: Discussionmentioning
confidence: 47%
“…However, in cells with a high level of expression of exogenous fibrillarin, the protein cannot be detected in the intranucleolar regions and the antibodies labeled antigens only in the periphery of the nucleoli. Importantly, such strange peripheral staining was observed after the overexpression of fibrillarin (Sheval et al 2005) and also in normal, non-transfected cells after the immunocytochemical detection of nucleophosmin/B23 (Zatsepina et al 1997;Misteli 2008;Musinova et al 2011). Furthermore, using postembedding immunoelectron microscopy in HeLa cells with specific antibodies, it was demonstrated that B23 was not localized to the nucleolar periphery but to the dense fibrillar component and the granular component (Biggiogera et al 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5E). It has previously been shown that adding a nonapeptide containing 9 basic amino acids to the C terminus of GFP allows nucleolar accumulation of the protein, not through a specific NoLS motif, but presumably through nonspecific, electrostatic interactions with negatively charged nucleolar components (9). There are 8 basic amino acids within the AAP2BR1-AAP2BR2 segment, and there are 10 basic residues in AAP2mt22 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importin-␤ mediates nuclear entry of the heterotrimer through the nuclear pores by its increasing affinity for nucleoporins along the inside of the nuclear pore complex (8). If the cargo protein also contains an NoLS, it can then be targeted to the nucleolus through charge-based interactions (9) or interactions with nucleolar proteins (10,11), although the specific requirements defining nucleolar localization are not as well understood as those for nuclear import.…”
mentioning
confidence: 99%